Occupation and 20 ans après: Representing Jewish Dissent in Montreal, 1967-1977 - Schwartz, Stephanie Tara (Canadian Jewish Studies / Études juives canadiennes, 2017)
Two NFB documentaries, Bill Reid’s Occupation (1970) and Jacques Bensimon’s 20 ans après (1977) offer an opportunity to reflect on the diverse politics of Montreal Jews during and following Quebec’s Quiet Revolution. Reading these films together, I argue that Montreal Jewish artists and activists should be considered in relation to the complex local and international politics of postcolonial dissent that marked the late 1960s and early 1970s, and that their experiences defy the narrow confines of a ‘third solitude’.